Kajian Poskolonialisme dalam Novel Helen dan Sukanta Sebagai Sarana Pembentukan Karakter Nasionalisme pada Siswa (Indo-MathEdu Intellectuals Journal, 2025)
This article will examine Pidi Baiq's novel Helen dan Sukanta using a postcolonialism approach. The study focuses on forms of hybridity and mimicry in the novel Helen dan Sukanta and their role as a means of shaping nationalism character in students. This research employs a qualitative descriptive method, with a literary postcolonialism approach. The research data consists of forms of mimicry and hybridity in Pidi Baiq's novel Helen dan Sukanta, as well as their connection to the formation of students' nationalism character. The data analysis process is conducted interactively, involving three stages: data reduction, data presentation, and conclusion drawing. The results of the postcolonialism study on Pidi Baiq's novel Helen dan Sukanta indicate that there are three forms of hybridity, consisting of (1) education and (2) attitude. The findings also reveal three forms of mimicry: (1) language, (2) appearance, and (3) weapons. The results of this study can also serve as a means of fostering nationalism character in students, as the postcolonialism analysis contains nationalist values. The formation of nationalist character through postcolonial studies can be integrated into Indonesian language subjects at the junior high school level and advanced Indonesian language courses at the senior high school level.